2022
DOI: 10.3390/nano12030417
|View full text |Cite
|
Sign up to set email alerts
|

CeO2-Promoted PtSn/SiO2 as a High-Performance Catalyst for the Oxidative Dehydrogenation of Propane with Carbon Dioxide

Abstract: The oxidative dehydrogenation of propane with CO2 (CO2-ODP) has been extensively investigated as a promising green technology for the efficient production of propylene, but the lack of a high-performance catalyst is still one of the main challenges for its industrial application. In this work, an efficient catalyst for CO2-ODP was developed by adding CeO2 to PtSn/SiO2 as a promoter via the simple impregnation method. Reaction results indicate that the addition of CeO2 significantly improved the catalytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…DFT calculations are consistent with the experimental studies (Figure 6), where the CÀ H activation energy on Fe 3 Ni (111) was lower than that of the CÀ C bond. In contrast, an opposite trend was observed for the Pt (111) and Ni 3 Pt (111). To better understand the reaction pathway of the Ni 3 Fe catalyst, the FeO-Ni interfacial active site structure was further investigated because iron oxide was observed by an in situ characterization of the Fe 3 Ni catalyst.…”
Section: Bimetallic Catalystssupporting
confidence: 88%
See 2 more Smart Citations
“…DFT calculations are consistent with the experimental studies (Figure 6), where the CÀ H activation energy on Fe 3 Ni (111) was lower than that of the CÀ C bond. In contrast, an opposite trend was observed for the Pt (111) and Ni 3 Pt (111). To better understand the reaction pathway of the Ni 3 Fe catalyst, the FeO-Ni interfacial active site structure was further investigated because iron oxide was observed by an in situ characterization of the Fe 3 Ni catalyst.…”
Section: Bimetallic Catalystssupporting
confidence: 88%
“…DFT calculations are consistent with the experimental studies (Figure 6), where the CÀ H activation energy on Fe 3 Ni (111) was lower than that of the CÀ C bond. In contrast, an opposite trend was observed for the Pt (111) and Ni 3 Pt (111).…”
Section: Bimetallic Catalystssupporting
confidence: 88%
See 1 more Smart Citation
“…Previous work in propane dehydrogenation over ceria supported catalysts primarily focuses on the interaction between Pt and Sn species, which were introduced into ceria supports by conventional co‐impregnation method [24] . And the effects of Ce as promoter on supported PtSn catalysts were also reported [25,26] . However, understanding of the interaction among Pt, Sn species and ceria support is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…[24] And the effects of Ce as promoter on supported PtSn catalysts were also reported. [25,26] However, understanding of the interaction among Pt, Sn species and ceria support is still limited. For CeO 2 -based catalysts, metal-doping has been used as an efficient way to enhance the formation of oxygen vacancies and it was found that Sn doping significantly improves the oxygen vacancy concentrations of CeO 2 in our previous work.…”
Section: Introductionmentioning
confidence: 99%